Photovoltaic Array Modeling under Uniform Irradiation and Partial Shading Condition - Lunde Ardhenta; Wijono Wijono (Institute of Advanced Engineering and Science, 2017)
Wind energy and solar energy are the prime energy sources which are being utilized for renewal energy. The performance of a photovoltaic (PV) array for solar energy is affected by temperature, irradiation, shading, and array configuration. Often, the PV arrays are shadowed, completely or partially, by the passing clouds, neighboring buildings and towers, trees, and utility and telephone poles. Under partially shaded conditions, the PV characteristics are more complex with multiple peaks, hence, it is very important to understand and predict the MPP under PSC in order to extract the maximum possible power. This paper presents the development of PV array simulator for studying the I–V and P–V characteristics of a PV array under a partial shading condition. It can also be used for developing and evaluating new maximum power point tracking techniques, for PV array with partially shaded conditions. It is observed that, for a given number of PV modules, the array configuration significantly affects the maximum available power under partially shaded conditions. This is another aspect to which the developed tool can be applied. The model has been experimentally validated and the usefulness of this research is highlighted with the help of several illustrations.